2014
DOI: 10.1007/s12155-014-9554-1
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Flocculation of Microalgae using Magnesium Hydroxide

Abstract: 23Flocculation of microalgae is a promising low-cost strategy to harvest microalgae for bulk 24 biomass production. However, residual flocculants can interfere in further downstream 25 processes or influence biomass quality. In this study, a new concept is demonstrated based on 26 reversible magnesium hydroxide flocculation, using Chlorella vulgaris and 27Phaeodactylum tricornutum as respectively a freshwater and a marine model species. We 28 show that flocculation was induced by precipitation of magnesium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 30 publications
3
35
3
Order By: Relevance
“…Repeated recycling of the culture medium after flocculation may result in depletion of magnesium from the medium. However, Vandamme et al 2014a demonstrated that 95 % of the precipitated magnesium hydroxide could be recovered by mild acidification, allowing it to be recycled back into the culture medium. The repeated addition of base to induce flocculation and of acid to neutralize the medium can result in accumulation of salts (Castrillo et al 2013).…”
Section: Autoflocculationmentioning
confidence: 99%
“…Repeated recycling of the culture medium after flocculation may result in depletion of magnesium from the medium. However, Vandamme et al 2014a demonstrated that 95 % of the precipitated magnesium hydroxide could be recovered by mild acidification, allowing it to be recycled back into the culture medium. The repeated addition of base to induce flocculation and of acid to neutralize the medium can result in accumulation of salts (Castrillo et al 2013).…”
Section: Autoflocculationmentioning
confidence: 99%
“…Magnesium coagulation followed by gravity sedimentation or flotation has been used for harvesting both marine and freshwater microalgae [12,13]. However, the interaction between Mg 2þ and microalgal cells and the effects of HPO 4 2À , CO 3 2À are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Vandamme et al [12] showed that 95% of precipitated magnesium hydroxide could be removed from the biomass with 5 M HCl (pH 7e8). In the present study, HCl was very effective in removing Al 3þ and Mg 2þ from the harvested biomass (Fig.…”
mentioning
confidence: 99%
“…Recently the pH-dependent reversibility of inorganic flocculants such as magnesium upon acidification has even been considered [35].…”
Section: Introductionmentioning
confidence: 99%